Emerging nanomedicine approaches fighting tumor metastasis: animal models, metastasis-targeted drug delivery, phototherapy, and immunotherapy. (22nd June 2016) - Liang, Chao; Xu, Ligeng; Song, Guosheng; Liu, Zhuang
Abstract : Nanomedicine approaches may bring new opportunities for tumor metastasis treatment. Abstract : Metastasis is directly or indirectly responsible for the majority of cancer deaths. Anti-metastasis treatment is thus the key to cure cancer. Recent development in nanomedicine has shown great promise for tackling cancer metastasis. In recent years, nanoparticle-based drug delivery systems have been extensively explored for improving cancer treatment, showing the ability to reduce the risk of tumor metastasis compared with conventional chemotherapy. Photothermal therapy, by employing nano-theranostic agents, has also been found to be able to inhibit lymphatic tumor metastasis. Moreover, the post-immunological effects of certain types of nano-therapies may also be utilized to treat tumor metastasis, presenting an exciting new avenue towards successful cancer treatment. In this review article, we would like to summarize the latest research advances in the development of various emerging nanomedicine approaches for cancer metastasis treatment, and discuss future prospects in this emerging field as well as the clinical translation potential of these techniques.